Margaret Atwood’s Surfacing: Quest For the Other, Finding the Self (Philologia, 2021)
The paper examines Margaret Atwood’s novel Surfacing as her contribution to the understanding of the concept of Other, especially in relation to Canadian identity and feminine experience. The research is primarily focused on the psychoanalytical and philosophical background of the novel and discovers in it traces of Lacan’s, Lévinas’, and Hegel’s works on the idea of Other and otherness, as well as Husserl’s intersubjectivity, or the duality of Self and Other. The psychoanalytical and philosophical approach will show that Atwood portrayed her main character as having a doppelgänger/the Other in Canadian wilderness, a major symbol in Atwood’s works, with which the narrator of the novel must reconcile and in so doing reconnect with what was lost, i.e. the bond with Mother Nature, the foremost part of the characteristic Canadian signature.
Keywords: M. Atwood; Surfacing; Self; Other/otherness; identity; madness; psychoanalysis; philosophy